2021
DOI: 10.1007/s11606-021-06954-8
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Is Associated with Cognitive Impairment, All-Cause Dementia, Vascular Dementia, and Alzheimer’s Disease: a Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Atrial fibrillation (AF) is a risk factor for cognitive impairment and dementia in patients with stroke history. However, the association between AF and cognitive impairment in broader populations is less clear. OBJECTIVE: To systematically review and quantitatively synthesize the existing evidence regarding the association of AF with cognitive impairment of any severity and etiology and dementia. METHODS: Medline, Scopus, and Cochrane Central were searched in order to identify studies investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 69 publications
1
33
0
Order By: Relevance
“…Furthermore, studies have revealed a strong association between rs9923231 , a gene encoding vitamin K epoxide reductase subunit 1, and VD [ 83 ]. Atrial fibrillation may also increase the risk of dementia, including not only VD, but also cognitive impairment and AD [ 84 ].…”
Section: Zinc and Vascular Dementiamentioning
confidence: 99%
“…Furthermore, studies have revealed a strong association between rs9923231 , a gene encoding vitamin K epoxide reductase subunit 1, and VD [ 83 ]. Atrial fibrillation may also increase the risk of dementia, including not only VD, but also cognitive impairment and AD [ 84 ].…”
Section: Zinc and Vascular Dementiamentioning
confidence: 99%
“…Heart failure is an independent risk factor for dementia, associated with a 28% relative odds increase in risk. Hypertension is also major risk factor for atrial fibrillation, which, in turn, is associated with an increased risk of cognitive impairment (48), mediated largely though the risk of thromboembolism. In a meta-analysis of 43 cohort studies, atrial fibrillation was associated with a 50% increase in relative odds of cognitive impairment or dementia (OR 1.5; 1.4-1.8).…”
Section: Cardiac Diseasementioning
confidence: 99%
“…In addition, in a meta-analysis including forty-three studies, AF was associated with dementia (OR 1.6; 95% CI 1.3–2.1) and the composite of cognitive impairment or dementia (OR 1.5; 95% CI 1.4–1.8) and these associations were independent of history of stroke. Interestingly, AF was associated with both vascular and Alzheimer’s dementia [ 108 ]. Stroke and silent or covert cerebral infarction appear to be the primary drivers of AF-associated cognitive decline [ 109 , 110 ].…”
Section: Neurological Complications Associated With Myocarditismentioning
confidence: 99%